Diffusion Tensor Imaging of the Hippocampal Formation in Temporal Lobe Epilepsy - Assaf, Bassam A.; Mohamed, Feroze B.; Abou-Khaled, Karine J.; Williams, J. Michael; Yazeji, May S.; Haselgrove, John; Faro, Scott H. (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Diffusion tensor imaging (DTI) is a noninvasive technique that can be used to assess the integrity of cerebral tissue. The purpose of this study was to assess DTI measurements in the hippocampal formation (HF) and to investigate the role of DTI in lateralizing the seizure focus in temporal lobe epilepsy (TLE).METHODS: We evaluated 12 patients with unilateral TLE and 14 healthy subjects. We collected diffusion-weighted images along six different directions with a b value of 1000 s/mm2, as well as an image acquired without diffusion weighting (b = 0 s/mm2). A 1.5-T imager was used to acquire 17 (3-mm) coronal sections covering the temporal lobes. We compared the mean diffusivity (trace D) and fractional anisotropy (FA) from symmetrical voxels by sampling the anterior HF bilaterally. We compared measurements with the EEG, high-resolution MR imaging, and clinical information.RESULTS: The patient group had significantly increased diffusivity and decreased FA in the HF ipsilateral to the seizure focus, as compared with values in the contralateral HF. When compared with healthy subjects, patients had significantly higher mean diffusivity in the ipsilateral HF; ipsilateral FA values were lower and did not reach statistical significance. Measurements in the contralateral HF did not show differences. Left-right and absolute diffusivity indices lateralized the abnormal HF in eight and five of 12 patients, respectively.CONCLUSION: Abnormal DTI measurements and the epileptogenic HF are associated in unilateral TLE. This finding may reflect hippocampal sclerosis and may aid in presurgical evaluation.